Exploring the environmental and economic impacts of wind energy: a cost-benefit perspective. Issue 8 (16th November 2020) - Adeyeye, Kehinde; Ijumba, Nelson; Colton, Jonathan
ABSTRACT: The transition from fossil fuel to a green economy has led to the rise of renewable energy sources. Wind energy stands out because it is free, clean, inexhaustible, has the capacity to generate greater power, and has lower energy costs. From local to global scales, the environmental effects of wind power are frequently positive, in contrast to the negative impacts associated with fossil fuel technologies. These include air pollution, climate change, health risks, high mortality rates, especially in infants, and greenhouse gas emissions. However, all energy sources have an impact on the environment and the economy including wind energy. With the rapid growth of wind energy over the last decade and the future potential of wind power generation, strategic assessment of these environmental and economic impacts, both positive and negative, and developing ways to mitigate these negative impacts are prerequisite operations to be carried out in the overall development of human-, economically- and ecologically-friendly wind energy.